HUBUNGAN ANTARA PERILAKU BELAJAR DENGAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN AQIDAH AKHLAK DI PESANTREN AL-URWATUL WUTSQAA BENTENG SIDRAP - Kalsum, Ummu; Nurfhadilah, Nurfhadilah (Inspiratif Pendidikan, 2017)
Abstrak: The purpose of this study, namely: 1) Describe the learning behavior in Pesantren Al-Urwatul Wutsqaa Fort Sidrap. 2) Describe the learning outcomes of learners on the Subject of Aqidah Akhlak in Pesantren Al-Urwatul Wutsqaa Fort Sidrap. 3) Knowing the behavior of learning with learners' learning outcomes on Subjects Aqidah Akhlak in Pesantren Al-Urwatul Wutsqaa Fort Sidrap. This thesis uses 205 pupolation that is all students class VIII MTs Al-Urwatul Wutsqaa Fort Sidrap and sample of 31 learners. The research instrument used is observation and note format. Data analysis technique used is quantitative descriptive analysis technique and using product moment. The average learning behavior of learners on subjects Aqidah Akhlak 84.3 lies in the interval of 81-100, which is in very good category. The average Learning Outcome of the learner is 72.5 which lies at intervals of 61-80, which are in either category. Learning behavior does not affect the students learning outcomes on subjects Aqidah Akhlak in Pesantren Al-Urwatul Wutsqaa Fort Sidrap.Hasil test t0 = 0.81 <from tt = 1.699. So it can be said that HO accepted and Ha rejected, meaning there is no relationship between learning behavior with learners' learning outcomes in the eyes of the Aqidah of Morals in Pesantren Al-Urwatul Wutsqaa Fort Sidrap.